Determination of Heavy Metals in Sediments of Masinga Reservoir, Kenya - Nzeve, Julius K.; Kitur, Esther C.; Njuguna, Steven G. (Journal of Environment and Earth Science, 2018)
In Kenya, heavy metal pollution in aquatic ecosystems due to anthropogenic activities cannot be underestimated. Therefore, an assessment of heavy metal contamination (Cu, Zn, Pb, Cr and Mn) in sediments of Masinga reservoir was carried out between January 2013 and December 2013 in five sampling sites. Heavy metal Concentrations were determined using atomic absorption spectrophotometer (AAS). The data obtained was analyzed using one way analysis of variance and significant differences accepted at p ≤ 0.05. Post Hoc Turkeys’ test was used to separate means. Mean heavy metal concentrations (mg/kg) in sediments were Cu (11.38 – 23.67), Zn (60.04 – 75.84), Pb (11.14 – 14.47), Cr (21.39-49.62) and Mn (259.12 – 642.30). There were significant differences in metal concentrations recorded for Cu, Cr, and Mn (p < 0.05) between the sites. The concentrations for all metals in sediments were lower than World Health Organization (WHO) set limit except for Cr at Tumutumu sampling site. The high Cr concentration is an indication of untreated or inadequately treated industrial and sewage wastes from the catchment.
Keywords: Heavy metals; Contamination; Sediments; Masinga reservoir